NANOG regulates epithelial–mesenchymal transition and chemoresistance in ovarian cancer. Issue 1 (10th January 2017) - Qin, Shan; Li, Yanfang; Cao, Xuexia; Du, Jiexian; Huang, Xianghua
Abstract : A key transcription factor associated with poor prognosis and resistance to chemotherapy in ovarian cancer is NANOG. However, the mechanism by which NANOG functions remains undefined. It has been suggested that epithelial-to-mesenchymal transition (EMT) also contributes to development of drug resistance in different cancers. We thus determined whether NANOG expression was associated with EMT and chemoresistance in epithelial ovarian cancer cells. NANOG expression was increased in epithelial ovarian cancer cell lines compared with its expression in normal epithelial ovarian cell lines. NANOG expression in SKOV-3 or OV2008 cells directly correlated with high expression of mesenchymal cell markers and inversely with low expression of epithelial cell marker. RNAi-mediated silencing of NANOG in SKOV-3 reversed the expression of mesenchymal cell markers and restored expression of E-cadherin. Reversibly, stable overexpression of NANOG in Moody cells increased expression of N-cadherin whereas down-regulating expression of E-cadherin, cumulatively indicating that NANOG plays an important role in maintaining the mesenchymal cell markers. Modulating NANOG expression did not have any effect on proliferation or colony formation. Susceptibility to cisplatin increased in SKOV-3 cells on down-regulating NANOG and reversible results were obtained in Moody cells post-overexpression of NANOG. NANOG silencing in SKOV-3 and OV2008 robustly attenuated in vitro migration and invasion. NANOG expression exhibited a biphasic pattern in patients with ovarian cancer and expression was directly correlated to chemoresistance retrospectively. Cumulatively, our data demonstrate that NANOG expression modulates chemosensitivity and EMT resistance in ovarian cancer.